2010
DOI: 10.1242/dev.051219
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Fgf and Bmp activities regulate the specification of olfactory sensory and respiratory epithelial cell fates

Abstract: SUMMARYThe olfactory sensory epithelium and the respiratory epithelium are derived from the olfactory placode. However, the molecular mechanisms regulating the differential specification of the sensory and the respiratory epithelium have remained undefined. To address this issue, we first identified Msx1/2 and Id3 as markers for respiratory epithelial cells by performing quail chick transplantation studies. Next, we established chick explant and intact chick embryo assays of sensory/respiratory epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
75
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(85 citation statements)
references
References 55 publications
9
75
1
Order By: Relevance
“…Tucker et al (2010) proposed that local FGF8 sources in the developing OP are responsible for specification and transition of primordial stem cells to terminally neurogenic precursors. However, the identity and location of these multipotent stem cells in the OP was still unclear Maier et al, 2010;Tucker et al, 2010). To follow neurogenesis and cell fate specification, the expression of neural and epidermal markers was analyzed with respect to expression of Fgf8.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Tucker et al (2010) proposed that local FGF8 sources in the developing OP are responsible for specification and transition of primordial stem cells to terminally neurogenic precursors. However, the identity and location of these multipotent stem cells in the OP was still unclear Maier et al, 2010;Tucker et al, 2010). To follow neurogenesis and cell fate specification, the expression of neural and epidermal markers was analyzed with respect to expression of Fgf8.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…To follow neurogenesis and cell fate specification, the expression of neural and epidermal markers was analyzed with respect to expression of Fgf8. SOX2 and PAX6 were used as stem/neural progenitor markers (Kawauchi et al, 2004), HuC/D was used as an early neuronal marker (Fornaro et al, 2003), while AP2␣, ID3, and MSX1 were used to identify epidermal cells Maier et al, 2010;Forni et al, 2011b). Analysis of knock-in mice expressing ␤-gal under direct control of Fgf8, Fgf8 nullLacZ /WT , confirmed that Fgf8 is expressed in the rostral portion of the invaginating OP [corresponding to the putative respiratory epithelium, (RE)], as well as in the epidermis proximal to the rim of the OP ( Fig.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
See 3 more Smart Citations